Legislative Change and Strike Activity in Canada, 1926-1974 - Frank, J.; Kelly, Michael; MacNaughton, Bruce (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1982)
The authors examine long term variations in the level of strike activity in Canada between 1926 and 1974 by examining the effects of several economic and organizational variables on the pattern of industrial conflict.